2017
DOI: 10.1186/s12875-017-0616-2
|View full text |Cite
|
Sign up to set email alerts
|

What do young Australian women want (when talking to doctors about contraception)?

Abstract: BackgroundAccess to most contraceptives in Australia requires a prescription from a doctor, and it has been shown that doctors can influence women’s decision-making with respect to contraception. However, little research has documented how women experience their interactions with doctors within the context of a contraceptive consultation. Understanding such experiences may contribute to our knowledge of factors that may influence women’s contraceptive decisions more broadly.MethodsWe report on findings from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 40 publications
2
38
0
1
Order By: Relevance
“…The authors described that, many times, the patients felt frustrated due to the limitations posed by their physicians or healthcare professionals, particularly when they are younger. 26 In general, healthcare professionals believe that there is a lack of interest by their patients concerning information about all contraceptive methods, and this can be a limiting factor for the use of LARCs. 15,27 In our study, 56% of the gynecologists believed that the women used the oral method inconsistently, forgetting 1 or more pills in the previous three months of use.…”
Section: Uncompliant Use Of the Short-acting Methodsmentioning
confidence: 99%
“…The authors described that, many times, the patients felt frustrated due to the limitations posed by their physicians or healthcare professionals, particularly when they are younger. 26 In general, healthcare professionals believe that there is a lack of interest by their patients concerning information about all contraceptive methods, and this can be a limiting factor for the use of LARCs. 15,27 In our study, 56% of the gynecologists believed that the women used the oral method inconsistently, forgetting 1 or more pills in the previous three months of use.…”
Section: Uncompliant Use Of the Short-acting Methodsmentioning
confidence: 99%
“…Healthcare provider beliefs about lack of interest may limit the extent to which they share information about all contraceptive methods and artificially limit use of LARCs [13]. The Contraceptive Use, Pregnancy Intentions and Decisions (CUPID) study of 3795 Australian women aged 18-23 years observed that women required consistent and accurate information that extended beyond OCs and often felt frustrated by the choice limitations imposed by their HCPs, particularly when they were seen to be linked to their age [31].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…A study among young Australian women (18-23 years) found that they perceived that doctors provided incomplete information about, and limited their options for, contraception because they were young. 12 A recent qualitative study involving young women (16-24 years) of culturally diverse backgrounds also suggested that clinicians may be selective about the contraception options they offer. 13 The uptake of long-acting reversible contraceptives has been slow among Australian women, despite them being recommended as first-line options for nulliparous ARTICLE Full text free online at nps.org.au/australian-prescriber Prescribing for adolescents women in Australia, the USA and the UK.…”
Section: Possible Biasmentioning
confidence: 99%